Reaktiovoimien, tukijalan kinematiikan sekä tulonopeuden yhteys heittosuorituskykyyn mies- ja naiskeihäänheittäjillä - Reinholm, Gia (2024)
Javelin throw involves a sequence of complex movements where the aim is to transfer momentum gained during approach run from the lower body to the upper body. Eventually the flow of kinetic energy is converted into javelin release velocity. At final foot strike the thrower decelerates this forward momentum, and during front foot contact high ground reaction forces are produced. Thrower’s approach velocity, javelin release speed and position during flight, braking action of the front leg, technical aspects of the throwing arm and posture of the thrower affect the throwing performance. However, the significance of ground reaction forces for the javelin throwing performance is not well-understood. The purpose of the study was to investigate whether ground reaction forces, front leg kinematics and approach velocity are associated with throwing performance in male and female javelin throwers. 11 male (age 24 ± 3 years, height 184 ± 8 cm, body mass 96 ± 12 kg, personal record 76.76 ± 5.43 m) and 13 female (age 25 ± 6 years, height 171 ± 5 cm, body mass 80 ± 11 kg, personal record 55.79 ± 5.85 m) javelin throwers were instructed to perform six maximal javelin throw attempts indoors. Ground reaction forces were measured with force platforms, and horizontal and vertical peak force, impulse and loading rate were analyzed. 3D motion analysis was performed to determine release parameters, kinematic variables and approach velocity. Theoretical throwing distance was calculated based on throwing parameters. For male throwers horizontal normalized peak force was associated with theoretical throwing distance (r = -0.636, p = 0.035), javelin release velocity (r = -0.609, p = 0.047) and pull distance (r = -0.624, p = 0.040). Delivery step length was associated with vertical (r = 0.674, p = 0.023) and horizontal peak force (r = -0.840, p = 0.001) and normalized horizontal peak force (r = -0.818, p = 0.002). For female throwers ground reaction forces did not correlate with throwing performance directly, but release height was associated with vertical (r = 0.721, p = 0.005) and horizontal (r = -0.607, p = 0.028) peak forces. Javelin release speed was associated with delivery step length (r = -0.560, p = 0.046) and ankle height at back foot contact (r = 0.582, p = 0.037). Approach velocity was not associated with throwing performance. For both genders horizontal braking might be more significant for throwing performance compared to vertical direction. Male throwers may need to increase horizontal braking to optimize throwing distance, javelin release velocity and pull distance while regulating vertical impact to control javelin position. Braking action can be emphasized with longer delivery step length and with greater approach velocity the demand for braking action increases. For female, peak forces might explain throwing performance indirectly. Female throwers should be able to produce enough force to support high pelvis posture and release height. Heel-dominant front foot technique might enhance braking action. To reach the optimal javelin release speed, delivery step length should not be overemphasized.